PENINGKATAN SIKAP KERJASAMA MELALUI BELAJAR KELOMPOK DALAM PEMBELAJARAN MATERI PECAHAN KELAS V SD MUHAMMADIYAH 1 BABAT - Oriza Zativalen; Tumardi Tumardi; Suhartono Suhartono (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2022)
The attitude of cooperation is needed in everyday life . First humans as social beings . Moral crisis into an attraction that lately seen as the root of the problems being faced by the nation of Indonesia. The point of social attitudes such as mutual cooperation , caring for each other , working as a team responsibility to develop as Indonesians less. Instead indeed more familiar with the selfish attitude, individualist , indifference , lack of responsibility, lazy communicate and interact with the social community. Moral education in the form of cooperation can be implemented at all levels of education, including elementary school level. Lack of cooperation attitude occurred in SD Muhammadiyah 1 tripe. VA grade students at the elementary Muhammadiyah 1 tripe about the attitude of cooperation . The emergence of such students because teachers teach traditional. This research seeks to develop learning with study groups to improve the collaborative attitude of students. Measures study groups namely , (1) serve the purpose, (2) form a heterogeneous group, (3) group discussion , ( 4 ) class discussion , ( 5 ) quiz ( 6 ) evaluation . Qualitative research approach that is the kind of scrutiny of class action. VA grade students performed at SD Muhammadiyah 1 Babat with 10 male and 10 female . Preliminary data on student attitudes to work with his friend showed 34 % . The study applied cluster cycle data I encounter one that is 69.5 % and 70.8 % ie 2 meeting . Cycle II encounter one that is 75.17 % and 79.5 % ie 2 meeting . Cycle III as convincing data to yield 81.7 %. Thus learning by studying clusters can enhance cooperation attitude SD Muhammadiyah 1 Babat and this step is not just based on certain subjects. The proposed changes from the data that the influence of frequently asked questions on the acquisition of advanced student understanding and cooperation with developing indicators Bloom theoretical level 4 and 5 that is to organize and act consistently , social influence student societies in collaboration with school students in learning activities.